ANALISIS PENGARUH MOTIVASI, LOKASI, DAN KUALITAS LAYANAN TERHADAP KEPUTUSAN PEMILIHAN FITNESS CENTER SEBAGAI TEMPAT MELATIH KEBUGARAN TUBUH (Studi Kasus Pada Oryza Gym Fitness Center Semarang) - Debbi Widya Kusumasari; Bambang Munas Dwiyanto (JURNAL STUDI MANAJEMEN ORGANISASI, 2014)
The Issues that form the basis of this analysis is the number of new members in OryzaGym Fitness Center is fluctuating every month. Several months have increased thenumber of new members, but there are some months which decreased from the previousmonth.Some promotions have been done by Oryza Gym Fitness Center to be known to thepublic, among others, by spreading leaflets, putting up banners and billboards, and alsoput up signposts Oryza Gym locations.The aims of this research are to determine the effects of motivation, location, and servicequality toward the selection decision of Oryza Gym Fitness Center as a fitness exercise.The data of this research is collected from 100 customers who are members of the OryzaGym Fitness Center.The sampling technique of this research is non probability sampling with the method ofaccidental sampling. The analysis techniques used in the research are validity test,reliability test, classic assumptions test, multiple linear regression analysis andhypothesis test including the t test, F test, and coefficient of determination (R2).The result of analysis using multiple linear regression can be seen that the variablemotivation, location, and service quality has positive influence on the selection decisionOryza Gym Fitness Center. Based on statistical data analysis, the indicators in this studyare valid and variables are reliable. In the classical assumption test, the regressionmodel is free multicollonierity, the heteroscedasticity does not occur, and normaldistribution. Individual sequence of each of the most influential variable is the variableservice quality and then location, while the less influential is the variable of motivation.The result of analysis using coefficient of determination is known that 56,7% of selectiondecision variable explained by the variation from motivation variable, location variable,and service quality variable, while 43,3% explained by others variable that excluded inthis research.Keywords: Selection Decision, Motivation, Location, Service Quality